Sarcopenia, Depressive Symptoms, and Fall Risk: Insights from a National Cohort Study in the Chinese Population - Zhang X; Ye D; Dou Q; Xie F; Zeng R; Zhu K; Zhu W; Zhu A; Chen L; Wu Y; Fan T; Peng P; et al. (Risk Management and Healthcare Policy)
Xiaoming Zhang,1,* Dongmei Ye,2,* Qingli Dou,1,* Fayi Xie,2 Rui Zeng,2 Ke Zhu,2 Wan Zhu,2 Aizhang Zhu,3,4 Lihuan Chen,5 Yishan Wu,2 Tenghui Fan,2 Pai Peng,2 Yuxu Huang,3,4 Shunrui Xiao,2 Jiahui Bian,2 Mengxia Shi,2 Jiang Wang,3,4 Wenwu Zhang1 1Department of Emergency, The People’s Hospital of Baoan Shenzhen, Shenzhen, Guangdong province, People’s Republic of China; 2School of Clinical Medicine, Jinggangshan University, Ji’an, Jiangxi Province, People’s Republic of China; 3School of Basic Medicine, Jinggangshan University, Ji’an, Jiangxi Province, People’s Republic of China; 4Online Collaborative Research Center for Evidence-Based Medicine Ministry of Education, Jinggangshan University Branch, Ji’an, Jiangxi Province, People’s Republic of China; 5School of Chinese Medicine, Jinggangshan University, Ji’an, Jiangxi Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaoming Zhang, Department of emergency, The People’s hospital of Baoan Shenzhen, Shenzhen, Guangdong province, People’s Republic of China, Email zhangmuxi0310@163.com Jiang Wang, School of Basic Medicine, Jinggangshan University, Ji’an, Jiangxi Province, People’s Republic of China, Email 9920070082@jgsu.edu.cnBackground: Previous investigations have indicated that both sarcopenia and depressive symptoms are linked to a heightened risk of falls. However, the potential synergistic effect of these conditions on fall risk remains unclear. This study aims to assess the combined influence of sarcopenia and depressive symptoms on the occurrence of falls in the Chinese population.Methods: The analysis included 8,405 participants from the China Health and Retirement Longitudinal Study (CHARLS), conducted from 2011 to 2015. Sarcopenia was confirmed using the 2019 Asian Working Group for Sarcopenia (AWGS) algorithm consisting of muscle strength, appendicular skeletal muscle mass (ASM), and physical performance. ASM was calculated using the formula: 0.193 × weight (kg) + 0.107 × height (cm) - 4.157 × sex - 0.037 × age (years) - 2.631. The Center for Epidemiological Research Depression Scale was utilized to assess depressive symptoms, with a cut-off score of 12 points. Depressive sarcopenia is defined as the coexistence of sarcopenia and depression. Multiple logistic regression analyses were conducted to explore the associations among sarcopenia, depressive symptoms, and fall occurrences.Results: During the four-year follow-up, 1,275 participants reported experiencing falls. A significant synergistic effect was identified between sarcopenia and depressive symptoms regarding fall risk. Compare to robust individuals, those with sarcopenia alone or depression alone had increased falls risks, but those with both conditions exhibited the highest fall risk, with adjusted odds ratios (OR) of 1.21 (95% CI 1.03, 1.42; P = 0.0174), 1.53 (95% CI 1.24, 1.88; P < 0.001), and 1.78 (95% CI 1.48, 2.15; P < 0.001), respectively.Conclusion: The findings highlight a synergistic effect between sarcopenia and depressive symptoms on fall risk. This study highlights the importance of early detection and intervention for both conditions, especially in older and middle-aged individuals, to mitigate fall risk.Keywords: sarcopenia, depression, falls, Chinese people